2021
DOI: 10.1080/19420862.2021.1958663
|View full text |Cite
|
Sign up to set email alerts
|

Development of potent and effective synthetic SARS-CoV-2 neutralizing nanobodies

Abstract: The respiratory virus responsible for coronavirus disease 2019 (COVID-19), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected nearly every aspect of life worldwide, claiming the lives of over 3.9 million people globally, at the time of this publication. Neutralizing humanized nanobody (V H H)-based antibodies (V H H-huFc) represent a promising therapeutic intervention strategy to address the current SARS-CoV-2 pandemic and provide a powerful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The most common strategy in the design of the hypervariable regions is to leave CDR1 and CDR2 at a fixed length each, whereas CDR3 may be represented by several different lengths, especially in the most recently reported libraries [ 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 22 , 23 ]. In most cases, the variability of CDRs 1 and 2 is set to represent the amino acid variability found in natural Nb repertoires.…”
Section: Structural Bases For the Design Of Synthetic Nb Librariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common strategy in the design of the hypervariable regions is to leave CDR1 and CDR2 at a fixed length each, whereas CDR3 may be represented by several different lengths, especially in the most recently reported libraries [ 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 22 , 23 ]. In most cases, the variability of CDRs 1 and 2 is set to represent the amino acid variability found in natural Nb repertoires.…”
Section: Structural Bases For the Design Of Synthetic Nb Librariesmentioning
confidence: 99%
“…That is why the number of Nb binders and their affinity values are generally higher in immune libraries [ 7 ]. However, recent works have shown that synthetic libraries can yield high affinity Nbs against different antigens, comparable to those obtained from immune libraries [ 12 , 14 , 20 , 22 ].…”
Section: Advantages and Limitations Of Synthetic Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic nanobodies (sybodies) are small, aerosolizeable, and heat stable, making them a viable candidate for COVID-19 prevention and treatment [ 79 ]. Stefan et al [ 118 ] created a massive synthetic VHH library (3.18 Ă— 10 10 ) and identified more than 50 VHH candidates that can bind to SARS-2 [ 6 ]. Schoof et al [ 119 ] used a synthetic Nbs library to identify a panel of Nbs that can bind to multiple epitopes on Spike.…”
Section: Camel Nanobodiesmentioning
confidence: 99%
“…The dire results have come despite ambitious and comprehensive response measures; at least on paper, the strict pattern of action has failed to mitigate the impact of this pandemic (Cabana et al, 2021). Then the situation was tense again when COVID-19 mutated from the novel Coronavirus (for example, the Delta and Kappa variants), which became an additional threat for the upcoming season in various countries (Stefan et al, 2021), including Indonesia, which was confirmed in June 2021 (Hasibuan, 2021). Therefore, this public health emergency requires more than just a health and medical care response, requiring the involvement of all citizens, targeted action from governments at all levels, and the implementation of multi-stakeholder policies (Bernard et al, 2021).…”
Section: Introductionmentioning
confidence: 99%